PERBANDINGAN ANTARA ECONOMIC VALUE ADDED DAN RETURN ON ASSET DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN - Putro, Muhammad Reza; Putra, R. Aditya Kristamtomo (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
In 2015 the automotive industry experienced a setback due to the economic crisis experienced by the world and in the following year it experienced a gradual increase, in this case researchers are interested in examining the increase in company performance. This study aims to determine the financial performance of automotive and component companies by comparing the measurement tools using Economic Value added (EVA) and Return on Assets (ROA) methods to determine the company's performance in Automotive and Component companies. This research method uses descriptive quantitative method with an approach using the method of Economic Value Added (EVA) and Return On Asset (ROA). Using financial statement data from 2016-2019. Based on the results of research from twelve companies, there are those that show the same movement and some are different, and it can be concluded that there are seven companies that show good financial performance and there are five companies that show poor financial performance